CARRYOVER AND POPULATION BUILD-UP OF INSECT PREDATORS IN RICE-WHEAT SYSTEM - M. Ramzan; M. Akhter; A. Rehman; M. Salim (Journal of Animal and Plant Sciences, 2007)
Carryover and population build-up of predators of insect pests in rice-wheat system were studied under zero tillage and conventional wheat planting methods at Muridke (District Sheikhupura) and Bhalwal (District Sargodha). Population of predators at both the sites remained high throughout the study period in wheat fields sown with zero-till drill than the wheat fields sown conventionally. Populations of spiders and rove beetles (Paederus fuscipes Curt) were significantly higher than the remaining species of the predators. The magnitude of the difference in the populations of predators between zero tillage and the conventional method of sowing of wheat increased with the passage of time at both the sites. Such difference was less during the first year (2003), but increased in
Keywords: predators of insect pests; rice; spiders and rove beetles